Lagrange 101

A particle moves according to the following Lagrangian .

L = 1 2 m ( x ˙ 2 + y ˙ 2 ) m g y \large{L = \frac{1}{2} m \, (\dot{x}^2 + \dot{y}^2 ) - m g \, y}

What are the accelerations of x x and y y ?

( x ¨ , y ¨ ) = ( 0 , g ) \large{(\ddot{x},\ddot{y}) = (0,- \sqrt{g})} ( x ¨ , y ¨ ) = ( 0 , g ) \large{(\ddot{x},\ddot{y}) = (0,-g)} ( x ¨ , y ¨ ) = ( 0 , g ) \large{(\ddot{x},\ddot{y}) = (0,g)} ( x ¨ , y ¨ ) = ( g , 0 ) \large{(\ddot{x},\ddot{y}) = (-g,0)}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Brian Moehring
Jul 12, 2018

Note that t L r ˙ = L r \frac{\partial}{\partial t} \frac{\partial L}{\partial \dot{r}} = \frac{\partial L}{\partial r}

Evaluating each side: t L r ˙ = t ( m x ˙ , m y ˙ ) = ( m x ¨ , m y ¨ ) \frac{\partial}{\partial t} \frac{\partial L}{\partial \dot{r}} = \frac{\partial}{\partial t}\left(m\dot{x}, m\dot{y}\right) = \left(m\ddot{x}, m\ddot{y}\right) L r = ( 0 , m g ) \frac{\partial L}{\partial r} = \left(0,-mg\right) and setting them equal to one another m ( x ¨ , y ¨ ) = m ( 0 , g ) ( x ¨ , y ¨ ) = ( 0 , g ) m\left(\ddot{x},\ddot{y}\right) = m\left(0, -g\right) \implies \boxed{\left(\ddot{x},\ddot{y}\right) = \left(0, -g\right)}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...